Diversité horticole des jardins familiaux et déterminants socio-démographiques. Les jardiniers face à l’évolution des normes horticoles - Francesca Di Pietro; Stéphanie Gosset (Territoire en Mouvement)
Allotment gardens are both spaces where biodiversity is severely limited by horticultural practices, and spaces of great value for urban ecological networks and environmental education. In managing their plots, gardeners are faced with the dual pressure of two conflicting norms: the aesthetic model of the "beautiful" garden, carefully maintained and dedicated to food supply, and the requirement to produce healthy food, definied as pesticide-free. In this respect, the aim of this article is to explore the horticultural diversity of allotments, understood as the diversity of production (agro-diversity), and the diversity of horticultural practices implemented by gardeners, and to analyze their socio-demographic determinants. Through 150 direct interviews carried out in 35 allotment gardens in the Tours and Orléans conurbations, we highlight (i) the range of varieties grown, and emphasize its ornamental dimension, (ii) the diversification of horticultural practices, particularly in crop protection and weed control, around a few predominant practices. Our results also show the influence of the gardener's social background on agro-diversity and on the horticultural practices adopted, and the influence of the gardener's gender, residential situation and geo-cultural origin on agro-diversity. While agro-diversity is socially polarized, with gardeners from more affluent social backgrounds favouring it, and gardeners from poorer social backgrounds undermining it, this is not observed for pesticide use, which is not specific to a social milieu. Finally, our results suggest the presence, in allotments, of several populations of gardeners, representing different gardening models.